P-273 MK2 Inhibition Prevents Colitis-associated Cancer Progression. (February 2017) - Suarez-Lopez, Lucia; Merrick, Karl; Morandell, Sandra; Hernandez, Yuliana; Haigis, Kevin; Yaffe, Michael
Abstract : Background: Chronic inflammation predisposes patients to develop tumors. In particular, inflammatory bowel disease (IBD) patients have a high risk of developing colitis associated cancer (CAC). Inflammatory cells produce cytokines that stimulate the growth and survival of malignant cells. In the case of CAC, several cytokines that contribute to cell transformation have been identified including IL-6, TNF-a and NF-kB dependent signaling, but additional cytokines and pathways likely also contribute. Stability and secretion of IL-6, IL-8, TNF-a and IL-1, along with recruitment of innate immune cells into the tumor are regulated by the p38/MAPKAPK2 (MK2) pathway. MK2 inhibition has been proposed previously as an anti-inflammatory strategy for treating IBD patients, but the exact role p38 pathway, and in particular MK2, in the development of inflammation-associated tumors remains to be elucidated. Methods: We have used a widely accepted method for modeling colitis in mice which consists in the administration of 2.5% DSS (dextran sodium sulfate) in the drinking water for 5 days followed by 4 days of recovery. This treatment results in mucosa ulceration and acute gut inflammation with high leukocyte infiltration. To mimic a chronic disease, this treatment is repeated from 3 to 5 cycles with resting periods of 21 days in between. AOM (azoxymethane) is administered as well at the beginning of the treatment to induce colitis associated cancer. Results: MK2 inhibition significantly inhibits tumor progression in a model of colitis-associated cancer in mice. MK2 KO animals develop smaller tumors in AOM/DSS driven colon cancer. However, MK2 depletion results in a dramatic increased susceptibility to DSS in the acute phase of the treatment, in contrast to expected from its pro-inflammatory role in other contexts. Conclusions: These preliminary results discourage MK2 inhibition to treat acute colitis, but support the use of MK2 inhibitors to prevent tumor progression under chronic inflammation.